FAKTOR-FAKTOR YANG BERKAITAN TERHADAP PROFITABILITAS PADA SUB SEKTOR MAKANAN DAN MINUMAN - Andreina, Regine Lindy; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2025)
This research aims to find out and find empirical evidence regarding the relationship between leverage, liquidity, and company size on profitability in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2019 – 2021. This research uses 29 food and beverage sub-sectors and sample companies were selected through purposive sampling technique with non-parametric test. The data processing technique uses the Spearman rank correlation test assisted by the SPSS (Statistical Product and Service Solution) program for Windows release 25 and Microsoft Excel 2019. The results of this study indicate that leverage has a negative, significant, and quite strong correlation. relationship with profitability, liquidity is positively correlated, significant, and has a fairly strong relationship with profitability, and firm size is positively correlated, significant, and has a fairly strong relationship with profitability.